2005
DOI: 10.1111/j.1523-1755.2005.67108.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional consequences of integrin-linked kinase activation in podocyte damage

Abstract: ILK regulates podocyte cell matrix interaction, proliferation, and slit membrane gene expression in podocyte damage. As this pathway is amendable to pharmacologic intervention, further detailed studies of in vivo ILK function in glomerular disease appear justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…Additionally, the established regulatory effect of increased ILK-1 expression on E-cadherin transcriptional expression (39) suggests an important role for this serine-threonine kinase in regulating E-cadherin expression in the early postinjury phase when whole-lung ILK-1 expression is increased. ILK-1-mediated E-cadherin repression and inhibition of GSK3␤ activity (40) has been implicated in EMT (41,42) and may explain in part the prominent epithelial and interstitial cellular proliferation to BHT/O 2 (15,16). Bailey and colleagues (43) have shown that peroxide-induced injury of cultured retinal pigment epithelial cells results in reduced junctional N-cadherin protein expression and ␤-catenin nuclear translocation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the established regulatory effect of increased ILK-1 expression on E-cadherin transcriptional expression (39) suggests an important role for this serine-threonine kinase in regulating E-cadherin expression in the early postinjury phase when whole-lung ILK-1 expression is increased. ILK-1-mediated E-cadherin repression and inhibition of GSK3␤ activity (40) has been implicated in EMT (41,42) and may explain in part the prominent epithelial and interstitial cellular proliferation to BHT/O 2 (15,16). Bailey and colleagues (43) have shown that peroxide-induced injury of cultured retinal pigment epithelial cells results in reduced junctional N-cadherin protein expression and ␤-catenin nuclear translocation.…”
Section: Discussionmentioning
confidence: 99%
“…LXA 4 did not affect Smad signaling, ILK induction or EMT induced by TGF-β 1 . Proposed mechanisms based on our and previous observations [12,26,29,30,37,39,48,49,50] on the signaling pathway involved in CTGF- and TGF-β 1 -induced EMT and the role of LXA 4 are summarized and illustrated in figure 8. Our results further expand on the antifibrotic repertoire of lipoxins [18], which represent useful tools for the development of a new treatment for renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence suggests that ILK is a critical mediator for tubular EMT induced by TGF-β 1 and CTGF [26,27,28], and likely plays a crucial role in podocyte damage, proteinuria and the pathogenesis of chronic renal fibrosis [29,30,31]. Forced expression of ILK in proximal tubular epithelial cells suppressed E-cadherin expression and induced fibronectin expression and its extracellular assembly [26].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that CD2AP also is expressed in the podocyte and that CD2AP is involved in maintaining the barrier function of the slit diaphragm by interacting with nephrin (24 -29). It also has been reported that the expression of CD2AP is decreased in cultured podocyte that is treated with PAN (30,31). All of the properties of these synaptic vesicle-associated molecules prompted us to consider that SV2B might be associated with the slit diaphragm.…”
mentioning
confidence: 99%